2020
DOI: 10.20947/s0102-3098a110
|View full text |Cite
|
Sign up to set email alerts
|

Condições de vida de famílias brasileiras: estimativa da insegurança alimentar

Abstract: O artigo objetiva estudar a associação entre condições de vida das famílias brasileiras e a estimativa da insegurança alimentar (IA). Para tanto, foi realizado estudo transversal conduzido com dados da Pesquisa de Orçamento Familiar (2008-2009), do IBGE, nas áreas rurais e urbanas. A estimativa da IA foi obtida a partir da pergunta: “das afirmativas a seguir, qual aquela que melhor descreve a quantidade de alimento consumido por sua família?”, quando a resposta foi “normalmente não é suficiente” ou “às vezes n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(29 reference statements)
2
5
0
3
Order By: Relevance
“…A high prevalence of quilombola households without adequate sanitation was also found, which indicates social vulnerability and deficient hygienic and sanitary conditions and infrastructure, which could compromise health due to infectious diseases [40]. An association between inadequate sanitation and FI in population-based studies has also been found by Santos et al [41] and Araújo et al [42]. This lack of basic sanitation is another indication of social inequalities and precarious living conditions, compromising the health of citizens by making them more susceptible to diseases attributable to inadequate sanitation.…”
Section: Discussionmentioning
confidence: 80%
“…A high prevalence of quilombola households without adequate sanitation was also found, which indicates social vulnerability and deficient hygienic and sanitary conditions and infrastructure, which could compromise health due to infectious diseases [40]. An association between inadequate sanitation and FI in population-based studies has also been found by Santos et al [41] and Araújo et al [42]. This lack of basic sanitation is another indication of social inequalities and precarious living conditions, compromising the health of citizens by making them more susceptible to diseases attributable to inadequate sanitation.…”
Section: Discussionmentioning
confidence: 80%
“…This value may be underestimated in view of a study by Porpino et al (2015) that points to high waste generation during the consumption stage in the lower-middle-class population, which can be associated with cultural traits, which differentiates Brazil from countries with equivalent per capita income in which loss in this stage are small. This situation is aggravated considering that about 39.4% of households in the country live in food insecurity (Araújo et al, 2020). Fur-thermore, 5% of all disease burdens in Brazil are associated with food shortages (GBD 2016Brazil Collaborators, 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Structural differences in the households of families in a situation of FI have also been identified in other studies. POF data analyses (2008)(2009) indicated that the prevalence of FI was associated with poor housing conditions, worse lighting, worse waste collection and sanitation services 25 .…”
Section: Discussionmentioning
confidence: 99%